An unusual presentation of atrial myxoma: thromboembolic phenomenon with a recent normal echocardiogram. Issue 9 (30th September 2019) - Rofe, Alexander; Fazio, Timothy N; Jones, Nicholas; Al-Kaisey, Ahmed M
Abstract : Atrial myxomas are the most common primary neoplasms of the heart. Clinical presentation varies from asymptomatic incidental masses to serious life-threatening cardiovascular complications. We describe the case of a 37-year-old man who presented with both coronary and cerebral embolisation secondary to an atrial myxoma in the context of a recent normal transthoracic echocardiogram.